Spontaneous coronary artery dissection causing acute coronary syndrome in a young patient without risk factors - Parag Chevli; Fnu Kelash; Pragnesh Gadhvi; Sreeram Grandhi; Amer Syed (Greater Baltimore Medical Center, 2014)
Spontaneous coronary artery dissection (SCAD) is a rare cause of acute myocardial infarction that is more common in younger patients (under age 50) and in women. Although the etiology is not known, some predisposing conditions to SCAD are well known and include Marfan syndrome, pregnancy and peripartum state, drug abuse, and some anatomical abnormalities of the coronary arteries such as aneurysms and severe kinking. We describe a case of SCAD in a young woman who presented with sudden onset of chest pain and was admitted for the treatment of acute coronary syndrome. The coronary angiography showed dissection of the left anterior descending artery. The patient underwent successful percutaneous transluminal coronary angioplasty and stent placement.